Pengaruh Penambahan Tepung Kacang merah pada Pembuatan Mie Basah Terhadap Komposisi Proksimat dan Daya Terima. - Sulistyowati, Erna, Eni Purwani, S.Si., M.Si, Pramudya Kurnia, STP, M.Agr (2013)
Background : The making of wet noodles can be done by mixing wheat flour and other flour. Red bean flour can be used as substituents of wheat flour because it contains higher protein than wheat flour that is 22.95%. Purpose : The purpose of this study is to evaluate the effect of red bean flour as an addition in the making of wet noodles on proximate composition and acceptability. Methods : The study design used was completely randomize designed that uses four additional variations (0%, 10%, 20%, and 30%). Data proximate composition and acceptance analyzed using statistical one way ANOVA test and followed by DMRT (Duncan's Multiple Range Test) with a level of 5%. Results : The results showed that there was significant effect of red bean flour addition to the water, fat and protein content of a wet noodle. The more red bean flour addition, the higher levels of water content in the wet noodle. Lowest fat content was shown on wet noodles with addition red bean flour 20%,that was 3.75%. Whereas, the highest fat content was shown in wet noodle with addition red bean flour 0% (control), that was 9.84%. The more red bean flour addition, the higher levels of a protein produced in the wet noodle. There was no significant effect of red bean flour addition to the ash of wet noodle. Levels of carbohydrate (by difference) were highest in the wet noodles by addition of red beans flour 0%, that was 43.85% and the lowest carbohydrate content was shown on a wet noodle with the addition of red beans flour 30%, that was 22.22%. There was effect of red bean flour addition on acceptance level of a wet noodle. Based on color, aroma, taste, texture and overall acceptance panelists favored addition was on the addition of red bean flour is 0% and 20%. Suggestion : By considering of proximate composition and acceptability, the making of wet noodles can use adding red bean flour 20%.